Study of Atrato river plume in a tropical estuary: Effects of the wind and tidal regime on the Gulf of Uraba, Colombia (2017)
This study focuses on the relative importance of the forcing agents of Atrato River plume as it propagates in a tropical estuary located in the Gulf of Uraba in the Colombian Caribbean Sea. Six campaigns of intensive field data collection were carried out from 2004 to 2007 to identify the main features of the plume and to calibrate and validate a numerical model. Field data and numerical models revealed high spatial and temporal plume variability according to the magnitudes of river discharges, tidal cycles, and wind stress. Atrato River discharge spreads over a considerable portion of the gulf, but only occupies the top 2 m of the surface layer. The tide modifies the position of the plume by inducing a horizontal migration of the salinity front during the day. Two principal modes of circulation in the gulf were identified under different wind conditions.